Pengaruh Peran Orang Tua, Guru, Dan Masyarakat Dalam Membentuk Kedisiplinan Ibadah Siswa Di MIN 4 Ponorogo - Radhiya Rasyada (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
In the education system there are three education centers which include education in the family environment which is carried out by parents, education in the school environment which is carried out by teachers, and education in the community environment which must synergize and be responsible for the education of the younger generation, including in terms of the discipline of student worship. By instilling the discipline of worship in children, it is hoped that there will be awareness and responsibility for worship in their daily lives and the formation of a stronghold in saving children's morals from bad behavior. This study aims to analyze the influence of parent’s role, teacher's role and community's role as well as the influence of the three roles simultaneously in shaping the discipline of student worship at MIN 4 Ponorogo. This research was conducted at MIN 4 Ponorogo by using quantitative research methods and correlation research design. The population in this study were 127 students in grades 4-6, 127 parents, 12 teachers and 24 leader communitier. The sampling technique used purposive sampling. Researchers took a sample of 73 people from each variable element as respondents to the research sample which consisted of 27 students, 27 student guardians, 7 teachers, and 12 leader communitier. Data analysis using partial and simultaneous correlational analysis. The results of the research concluded that the role of parents, teachers and the community had a very strong influence, both partially and simultaneously on the formation of student worship discipline at MIN 4 Ponorogo. Meanwhile, the simultaneous contribution or contribution of the role variables of parents, teachers and society to the formation of religious discipline of students at Min 4 Ponorogo is 95% and 5% is influenced by other variables